Effects of acupressure on progress of labor and cesarean section rate: randomized clinical trial - Reginaldo Roque Mafetoni; Antonieta Keiko Kakuda Shimo (Universidade de São Paulo, 2015)
OBJECTIVE To analyze the effects of acupressure at the SP6 point on labor duration and cesarean section rates in parturients served in a public maternity hospital. METHODS This controlled, randomized, double-blind, pragmatic clinical trial involved 156 participants with gestational age ≥ 37 weeks, cervical dilation ≥ 4 cm, and ≥ 2 contractions in 10 min. The women were randomly divided into an acupressure, placebo, or control group at a university hospital in an inland city in the state of Sao Paulo, Brazil, in 2013. Acupressure was applied to the SP6 point during contractions for 20 min. RESULTS The average labor duration was significantly different between the SP6 acupressure group [221.5 min (SD = 162.4)] versus placebo [397.9 min (SD = 265.6)] and versus control [381.9 min (SD = 358.3)] (p = 0.0047); however, the groups were similar regarding the cesarean section rates (p = 0.2526) and Apgar scores in the first minute (p = 0.9542) and the fifth minute (p = 0.7218) of life of the neonate. CONCLUSIONS The SP6 acupressure point proved to be a complementary measure to induce labor and may shorten the labor duration without causing adverse effects to the mother or the newborn. However, it did not affect the cesarean section rate.